Gastric transposition as a valid surgical option for esophageal replacement in pediatric patients: experience from three Italian medical centers. (4th May 2016) - Angotti, Rossella; Molinaro, Francesco; Noviello, Carmine; Cobellis, Giovanni; Martino, Ascanio; Del Rossi, Carmine; Bianchi, Adrian; Messina, Mario
Abstract : Background: Esophageal replacement in children is an option that is confined to very few situations including long-gap esophageal atresia and esophageal strictures unresponsive to other therapies (peptic or caustic ingestion). The purpose of our work was to describe the experience of gastric transposition in three Italian centers. Methods: This is a retrospective study. The data were extrapolated from a prospective database. We included all patients who had undergone gastric transposition in the last 15 years. Results: In the 15-year period, eight infants and children (3 males and 5 females) underwent gastric transposition for esophageal replacement. Six patients had long-gap esophageal atresia, and two had caustic esophageal stenosis. There were no deaths in the series. Three patients had an early postoperative complication: two had a self-limited salivary fistula at three weeks, and one (a patient with jejunostomy) had a jejunal perforation treated surgically. One late complication, anastomotic stricture, was recorded that required two endoscopic dilatations. The median follow-up was 60 months (range: 18–144 months). At final clinical follow-up, six patients had no eating problems, and two patients had some difficulties with eating (jejunostomy in situ), but they underwent logopedic therapy with improved outcomes. All patients had an increase in body weight and height postoperatively. Conclusion: Our small study reports the clinical experience of three Italian centers in which gastric transposition was performed with excellent results, both in terms of surgical technique (simplicity, reproducibility, complication rate) and clinical follow-up (good oral feeding of young patients, normal social life and regular growth curves).